2019
DOI: 10.12669/pjms.35.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among pediatric residents and junior consultants working at a tertiary care hospital

Abstract: Objective: To determine the burnout among postgraduate residents’ and junior consultants in a tertiary care hospital. Methods: This cross-sectional study was conducted among the postgraduate residents (PGR) and junior consultants (JC) working at The Children’s Hospital Lahore in 2018. Participants were asked to complete Copenhagen Burnout Inventory questionnaire about burnout on 5 point Likert scale. ‘100 (always), 75 (often), 50 (sometimes), 25 (seldom) and 0 (never/almost never or according to intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Based on previous findings, we explored the potential moderating effect of different sociodemographic and work-related variables, and surprisingly, none had a significant effect between the relation of burnout and mental health; even variables at the univariate level showed some significant differences. These results are in line with previous findings where the differences in separate samples were not conclusive [36,39,[51][52][53][54][55]. The role of sex, marital status, and suffering from a physical illness showed significant differences between groups in some of the indices; however, the effect sizes of those differences were not large enough to compromise the prediction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on previous findings, we explored the potential moderating effect of different sociodemographic and work-related variables, and surprisingly, none had a significant effect between the relation of burnout and mental health; even variables at the univariate level showed some significant differences. These results are in line with previous findings where the differences in separate samples were not conclusive [36,39,[51][52][53][54][55]. The role of sex, marital status, and suffering from a physical illness showed significant differences between groups in some of the indices; however, the effect sizes of those differences were not large enough to compromise the prediction.…”
Section: Discussionsupporting
confidence: 91%
“…Additional stressors during the COVID-19 pandemic are the inability to obtain protective equipment during routine clinical work [46,47] and the fear of infecting a loved one or being infected with COVID-19 [48][49][50]. However, the empirical evidence is not conclusive; as in some cases, these factors, including the number of working hours [51] or years of practice [52], did not show size effects similar to previous findings or a significant effect [39,[53][54][55].…”
Section: Burnout In Medical Residentsmentioning
confidence: 85%
“…Shazad et al stated the main factor of burnout as the lack of getting support from the work environment and family members. 10 , 11 Severe comorbidity of depression, anxiety and stress in health care workers was demonstrated by Ashraf et al 12 …”
Section: Introductionmentioning
confidence: 98%
“…Shazad et al stated the main factor of burnout as the lack of getting support from the work environment and family members. 10,11 Severe comorbidity of depression, anxiety and stress in health care workers was demonstrated by Ashraf et al 12 In the literature, many methods, mostly questionnaires, were used to evaluate the occupational burnout, job satisfaction and anxiety levels of employees. 4,13,14 Turkish EPs are facing with heavy work overloads because of overcrowding and also with abuse and injury because of patient and/or their relatives violence.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in literature are contradictory with regard to the levels of psychological distress among pediatricians as compared to other medical specialties. A study in Pakistan indicated that pediatricians have more psychological problems than other medical specialties [15], while other studies in the United States and Egypt found the opposite [16,17]. This can be due to differences in culture and healthcare systems between countries.…”
Section: Introductionmentioning
confidence: 98%